Finding out about nuclear energy - Doeden,Matt; Doeden,Matt (USA: Lerner Publications, 2014)
Did you know that tiny atoms that make up all matter hold huge amounts of energy? This energy, called nuclear energy, can power the television and refrigerator in your home. How is nuclear energy produced, though? And what are the drawbacks of this energy source? Read this book to find out all about nuclear energy
Keywords: Nuclear energy; TECHNOLOGY & ENGINEERING Mechanical